Challenges and Adaptation in Online Classes during the Pandemic among College Students in the Philippines and Indonesia - Santos, Cresencia M.; Evangelista, Gerald T.; Ryandini, Felicia Risca; Veranga, Maricar; Jazul, Regina; Tamayo, Josan (Future Science / FSH-PH Publications, 2024)
The technological breakthrough and the unprecedented pandemic largely impacted the educational system worldwide. The students’ experiences during this time affect their acquisition of the learning outcome and well-being. Although many studies have been conducted in this area, limited information is available on the correlation between the student’s challenges and adaptation between the two countries, the Philippines and Indonesia. Hence, this study attempts to fill in the void. The findings of this study revealed the following results: challenges encountered by the college students from the Philippines yielded a moderate extent (x̄=2.90; SD= 0.41) while the college students from Indonesia resulted to some extent (x̄=2.80; SD= 0.26); on adaptation, the college students from the Philippines showed a moderate extent (x̄=3.01; SD= 0.42) while the college students from Indonesia utilized adaptation to some extent (x̄=2.01; SD= 0.26). There is a positive correlation (0.153 and 0.485) between the schools in the Philippines and Indonesia. The variability in the college students’ responses may have been shaped by the different factors situated around him/her such as the availability of resources, type of learning platforms, computer literacy, student personality behavior towards learning, family structure, and the physical environment. The implications of the study on policy-making, programs on mental health, and future research are discussed.